Modulação da expressão de isoformas de lncRNA na resposta ao tratamento por metformina em diferentes tipos celulares - Izabela Mamede Costa Andrade da Conceição (2022)
Long non-coding RNAs (lncRNAs) are molecules with more than 200 nucleotides which do not code for proteins in canonical ways. They undergo splicing, since they possess introns and exons, and have multiple transcribed isoforms. On average lncRNAs have twice as many isoforms when compared to protein-coding genes. Nevertheless, for lncRNAs, as well as for mRNA, measurements of differential expression are routinely performed only at the gene level. Gene level analysis does not consider the multiple isoforms which arise from the transcription of a single gene, making the final differential expression results incomplete. Metformin is the first-line oral therapy for type II Diabetes and for several other diseases, including cancer. However, its mechanism of action remains not thoroughly explained, with its multiple effects as epigenetic regulator, anti-proliferation and anti-aging drug not explored at the molecular level. Global transcriptomic analyses using metformin in different cell types reveals that only protein-coding genes are normally taken into consideration. Our aim was to globally characterize lncRNA isoforms that were differentially affected by metformin treatment on multiple human cell types, and to provide insights into the lncRNA regulation by this drug. We selected data from all higher depth and paired-end stranded libraries publicly available. We selected six series for further exploration to perform a statistically comparable differential expression (DE) isoform analysis. We also inferred the biological roles for lncRNA DE isoforms using in silico tools. Sequence pseudo-alignment was performed with Salmon (v.1.5.0) and differential expression using Fishpond. Correlation, integration with epigenomic available datasets and transcript annotation were performed using packages in R and functional enrichment was performed with fgsea and integrated between all series. To our knowledge, this is the first study that globally analyzed lncRNA isoforms responsive to metformin treatment. We found the same isoform of a lncRNA (AC016831.6- 205) highly expressed in all six-metformin series, which has a second exon putatively coding for a peptide with relevance to the drug action in cancer. Moreover, other two lncRNA isoforms (ZBED5-AS1-207 and AC125807.2-201) may also behave as cis-regulatory elements to the expression of transcripts in their vicinity. Our results strongly reinforce the importance of taking into consideration DE isoforms of lncRNA for the understanding of metformin mechanisms at molecular level.